2000
DOI: 10.3141/1732-01
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Pavement Damage Due to Heavier Loads on Louisiana Highways: Preliminary Assessment

Abstract: A preliminary assessment is made of the impact of increasing the gross vehicle weight (GVW) from current legal limits to 100,000 lb (45 400 kg) on vehicles hauling sugarcane, rice, timber, and cotton. Sections of road were chosen in each area of Louisiana where commodities are produced, the amount of each commodity hauled was estimated, and the effects of increasing the GVW were evaluated for each section using pavement design models. Design data were secured from the Louisiana Department of Transportation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In 1998, Louisiana assessed increasing GVW to 100,000 lb on trucks carrying sugarcane, rice, timber, and cotton. The state identified road segments along which each commodity was produced, the number of trucks carrying each load, estimated the amount of each commodity hauled, and the potential effect of increasing the weight on those road segments over a 20-year period ( 11 ). Overall, increasing the GVW decreased the service life of roads, increased the cost of pavement overlays, and reduced the time between required overlays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 1998, Louisiana assessed increasing GVW to 100,000 lb on trucks carrying sugarcane, rice, timber, and cotton. The state identified road segments along which each commodity was produced, the number of trucks carrying each load, estimated the amount of each commodity hauled, and the potential effect of increasing the weight on those road segments over a 20-year period ( 11 ). Overall, increasing the GVW decreased the service life of roads, increased the cost of pavement overlays, and reduced the time between required overlays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, because the result was based on selected commercial industries, it was not applicable to general cases. Roberts and Djakfar (1999) conducted a preliminary assessment of impacts of increasing the GVW from the existing legal limit to 100 kips on trucks hauling sugarcane, rice, timber, and cotton. Issued by the Louisiana Department of Transportation and Development, the agronomic/ horticultural permit, the cotton module permit, and the harvest season or natural forest products permit were included in the study.…”
Section: B4 Axle-based Feementioning
confidence: 99%
“…Researchers found that smaller impacts resulted from increasing vehicle's GVW if the pavement was designed to haul a larger number of ESALs. Roberts and Djakfar (1999 Luskin et al (2002) discussed the economic inefficiency of the fee structure for HB 2060 permits, which are the annual divisible-load permits legislated by the Texas government in 1989 for trucks to operate above the general weight limits. Owing to the lack of detailed data on travel information, extreme-case scenarios for pavement damage (i.e., the worst-case scenarios and the best-case scenarios) were confined in the analysis.…”
Section: B4 Axle-based Feementioning
confidence: 99%
“…Fortowsky and Humphreys (2006) discovered important savings to the cost of resurfacing the pavement if higher limits of 45 tonnes (or 40 tonnes to special commodities) were allowed along the whole length of Maine's I-95, principally due to the decrease in the diversion of heavy trucks onto state roads. In this same vein, Roberts and Djakfar (2000) pointed out that the design of the pavement is very important in determining the additional cost for allowing heavier trucks. For the Belgian case, Debauche and Decock (2007) demonstrated that depending on the precise LHV configuration, the effects on the infrastructure could vary considerably.…”
Section: Effects On Infrastructurementioning
confidence: 99%